Entre o afeto e a violência : significados e experiências de violência nas narrativas autobiográficas de mulheres em vulnerabilidade - Freire, João Victor de Farias Furtado (2023)
This research delves into the topic of violence as a recurring phenomenon in human history, related to various societal and cultural aspects. With the emergence of scientific studies and the field of Public Health analyzing this subject, numerous questions have arisen, exploring the influence of violent acts on individual development. That said, the present research aims to comprehend the experiences of violence faced by socially excluded women, seeking assistance from a Civil Society Organization (CSO) in northeastern Brazil, through their life narratives. The study adopts a qualitative research approach, investigating the subject with an exploratory, descriptive, and analytical perspective. To grasp the phenomenon of violence and foster the creation of autobiographical narratives, a Biographical Reflective Circle (CRB) was implemented. This methodological device,facilitates the production of life narratives within a group setting through bonding and compassionate activities, centering around a focal question. The research involved 10 (ten) vulnerable women and mothers receiving aid from the Primeira Infância Institute (IPREDE), participating in the Vai Maria Project. The triggering question for their narratives was: “how did I become the woman I am today?”. By analyzing these narratives, we aimed to understand the essence and development of violence as well as examine how these women perceive violence within their own lives. The methodology employed for analyzing the narratives was the Textual Discursive Analysis - ATD. This approach facilitated the identification of categories constituting the phenomenon of violence within the experiences of these women, spanning from childhood to adulthood, revealing its intricacies and ramifications. Consequently, the memories and testimonials of these women emerge as the key protagonists in this research, elucidating the meanings of this phenomenon and its impact on the formation of Brazilian society, along with the social, cultural and political role of women. Through this research, the need for interaction of multiple knowledge was proven, in the investigative effectiveness of the field of Collective Health, as well as the development of reflections and methods in preventing and combating violence against women.